Hemorheological mechanisms for increased thrombosis in subjects using gestodene. Issue 12 (26th October 2018) - Swanepoel, Albe Carina; Roberts, Hildegarde Cecilia; Soma, Prashilla; Lindeque, Barend Gerhardus; Bester, Janette
Abstract: There are several possible mechanisms by which combined oral contraceptives (COC) use increase venous thromboembolism (VTE) risk. Melodene® is a monophasic COC containing the third‐generation progestin Gestodene (GSD), which is associated with increased risk of VTE. Therefore, the aim of this study was to investigate the possible alterations in viscoelastic parameters of whole blood and plasma clots along with the biophysical characteristics of erythrocytes and specifically fibrin fibers in females using a COC containing GSD. GSD appeared to have a significant impact on the biophysical characteristics of fibrin fiber networks. When GSD is combined with ethinylestradiol the viscoelastic properties of whole blood clots tend to become more prothrombotic. The alterations to and aggregation of erythrocytes accompanied with spontaneous formation of a fibrin "blanket" provides a possible mechanism for the increased occurrence of "red" clots, which can lead to occlusions in the vascular system. Thus, the increased risk of VTE associated with these COCs can be attributed to these erythrocyte‐and‐fibrin‐rich‐clots occluding venous vessels. However, our findings also propose that these changes to the biophysical properties of both erythrocytes and fibrin, specifically spontaneous expansion of deformed fibrin networks, can also occlude vessels in the microcirculation, which could have lasting, subclinical complications for female users. We recommend that a thorough risk assessment, with specific focus on coagulation and other factors affecting fibrin formation, be done for each female before prescribing a GSD‐containing COC. Females that "qualify" then need to be monitored on a regular basis to lower the risk of thrombotic events. Research Highlights: Gestodene in combination with ethinyl estradiol significantly impacts the biophysical characteristics of erythrocytes and fibrin fiber networks. These changes, specifically spontaneous expansion of deformed fibrin networks, can occlude vessels in the microcirculation, which could have lasting, subclinical complications for the female user. The changes observed for specifically erythrocytes and fibrin show that the hormone formulation investigated contribute to a thrombogenic profile for female users Abstract :